A method for calculating BMI z-scores and percentiles above the 95th percentile of the CDC growth charts - Rong Wei; Cynthia L. Ogden; Van L. Parsons; David S. Freedman; Craig M. Hales (Taylor & Francis Group, 2020)
Background The 2000 CDC growth charts are based on national data collected between 1963 and 1994 and include a set of selected percentiles between the 3rd and 97th and LMS parameters that can be used to obtain other percentiles and associated z-scores. Obesity is defined as a sex- and age-specific body mass index (BMI) at or above the 95th percentile. Extrapolating beyond the 97th percentile is not recommended and leads to compressed z-score values. Aim This study attempts to overcome this limitation by constructing a new method for calculating BMI distributions above the 95th percentile using an extended reference population. Subjects and methods Data from youth at or above the 95th percentile of BMI-for-age in national surveys between 1963 and 2016 were modelled as half-normal distributions. Scale parameters for these distributions were estimated at each sex-specific 6-month age-interval, from 24 to 239 months, and then smoothed as a function of age using regression procedures. Results The modelled distributions above the 95th percentile can be used to calculate percentiles and non-compressed z-scores for extreme BMI values among youth. Conclusion This method can be used, in conjunction with the current CDC BMI-for-age growth charts, to track extreme values of BMI among youth.